The Effect of Administering Ethanol Extract of Rambutan Leaves (Nephelium Lappaceum L.) on Accelerating The Healing of Excision Wounds In Male White Mice (Rattus Norvegicus) - Patimah Simamora (PT Inovasi Pratama Internasional, 2026)
Excisional wounds are wounds in which the skin surface and underlying layers are broken to varying depths but the wound edges are regular and are caused by accidental events such as accidents, trauma, or exposure to pressure, heat, sunburn, or chemicals. Rambutan leaves (Nephelium lappaceum L.) are known to contain secondary metabolite compounds, especially flavonoids and tannins, which have the potential to accelerate the healing of excisional wounds through antioxidant, anti-inflammatory, and astringent activities. This study aims to determine the effect of administering rambutan leaf ethanol extract on accelerating the healing of excisional wounds in male white rats (Rattus norvegicus) and to determine the most effective concentration. The parameters observed include the percentage of wound healing and epithelialization time. Data were analyzed using the One-Way ANOVA test with a 95% confidence level. The results of phytochemical screening showed that rambutan leaf ethanol extract contains flavonoids and tannins. The percentage of wound healing on the 14th day in the 20%, 25%, 30%, positive control, and negative control concentration groups was 87%, 90%, 95.45%, 93.10%, and 86%, respectively. The results of statistical analysis showed that there were significant differences between the treatment groups. On the 4th day, the F value was 4.842 with p = 0.007, on the 9th day, the F value was 6.524 with p = 0.002, and on the 14th day, the F value was 8.720 with p <0.000 (p <0.05). The concentration of 30% rambutan leaf ethanol extract provided the best wound healing activity with a healing percentage of 95.45% on the 14th day with a significant value of 0.000 (p<0.05) and the fastest epithelialization time was a concentration of 30% on the 6th day with a significant value of 0.018 (p<0.05) compared to other groups.